Analisis Kinerja Simpang Bersinyal Dengan Software Vissim : Studi Kasus Jl. Poros Malino - Jl. Usman Salengke – Jl. K.H. Wahid Hasyim - Qalbi, Nurul; Mallawangeng, Tamrin; Yunianti, Nurhadijah (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
The performance of an intersection is the feasibility condition of the intersection facility which is influenced by road capacity, traffic behavior, and the speed of a vehicle. The intersection being analyzed is Jl. Poros Malino - Jl. Usman Salengke – Jl. K.H. Wahid Hasyim. The purpose of this research is to find out the comparison of PTV Vissim and MKJI 1997 Software and to find out the results of alternative modeling in the performance analysis of the four signalized intersection Jl. Poros Malino - Jl. Usman Salengke – Jl. K.H. Wahid Hasyim. Based on the analysis and discussion it was concluded that the comparison of queue length using the vissim and MKJI software on the Jl. Usman Salengke Utara, namely 110 m and 112 m. It can be seen that the results of the analysis using the vissim software are closer to the conditions in the field, namely 92 m. Because vehicle behavior and the distance between vehicles can be adjusted in the vissim software, the analysis delay using vissim is superior because it can calculate each arm, while the MKJI calculation is only the average delay with service level F (very bad). And alternative simulation results with cycle time settings can be used as a solution to increase the performance of intersections where the level of service changes to E (bad) with a 13% decrease.